2022
DOI: 10.1111/jfbc.14117
|View full text |Cite
|
Sign up to set email alerts
|

Diet and lifestyle modifications for effective management of polycystic ovarian syndrome (PCOS)

Abstract: Polycystic ovarian syndrome (PCOS) is caused by abnormal production of androgens resulting in the formation of small fluid-filled sacs in the ovaries. This condition worsens the life quality of women by disturbing their physiology and psychology in reproductive age. PCOS may also be associated with other morbidities like diabetes and hypertension. Numerous factors like imbalanced dietary patterns, poor lifestyle activities, improper care and medication, late diagnosis, and ignorance are involved in the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Shahid et al ( 2022 ) found a significant improvement in LH levels in PCOS women after seed cycling. Studies identified a decrease in LH after seed cycling in PCOS women, which is consistent with our findings.…”
Section: Resultsmentioning
confidence: 99%
“…Shahid et al ( 2022 ) found a significant improvement in LH levels in PCOS women after seed cycling. Studies identified a decrease in LH after seed cycling in PCOS women, which is consistent with our findings.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of lifestyle modification, maintaining an appropriate diet is crucial. This involves primarily reducing the intake of high glycemic index carbohydrates, adopting a low-calorie diet, increasing fiber and polyunsaturated fat consumption, and decreasing saturated fats [3,18,35,36]. Another vital aspect of modifying the lifestyle of women with PCOS is regular physical exercise, which, when combined with an appropriate diet, can lead to a reduction in excessive body weight and alleviate bothersome PCOS-related symptoms, ultimately contributing to enhanced well-being.…”
Section: Discussionmentioning
confidence: 99%
“…This approach not only facilitates effective interviews but also contributes to formulating a treatment plan geared toward mitigating or addressing the prevailing symptoms and achieving the desired outcomes for the patient. Consequently, it is essential to delve into the quality of life experienced by women with PCOS and the prevalent challenges they encounter [14][15][16][17][18][19][20]. This includes exploring aspects such as family life, social interactions, sexual well-being, professional engagements, parenthood, fertility treatments, and potential feelings of helplessness linked to issues like hirsutism or accompanying metabolic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise, when properly performed in moderation and in conjunction with an anti-inflammatory diet such as the traditional Mediterranean diet, also has an essential role in preventing and fighting cancer, as has been shown by various epidemiological, observational, and meta-analysis studies [ 28 , 29 ]. Consistent exercise alters several biochemical markers associated with cancer cell metabolism [ 30 ].…”
Section: Physical Activity and Cancermentioning
confidence: 99%